Cooperative game theory approach for multi‐objective home energy management with renewable energy integration. Issue 1 (15th November 2018) - Lokeshgupta, Bhamidi; Sivasubramani, Shanmugavelu
Abstract : This study proposes a mathematical model of an intelligent multi‐objective home energy management (HEM) scheme with the integration of small‐scale renewable energy sources. The main aim of the proposed model is to handle the residential load demand in a smart way to minimise both the consumer's energy bill and the system peak demand simultaneously. To generate the best compromise solution of the proposed multi‐objective problem, a cooperative game theory approach is used in this study on the basis of super‐criterion and a Pareto optimal solution concept. In the cooperative game process, each HEM objective is assigned as a player and every player tries to maximise their own payoff. Bargaining model in the form of super criterion is considered in this game approach. Finally, all players can get win–win nature with collective negotiations. Generally, HEM method deals with various controllable devices having distinct operating characteristics. Because of this, the proposed HEM problem is modelled as a mixed‐integer problem. Consequently, a mixed‐integer non‐linear programming is applied in this game process to maximise the super‐criterion. To show the effectiveness of the proposed model, different case studies and various scenarios are carried out.